Development of a lifetime evaluation system and lifetime prediction method for GaN RF semiconductors used in manned and unmanned weapon systems - Youngrack Choi; Yunho Kang; Hyounggook Kim (선진국방연구, 2023)
The aim of this study is to develop a testing system that applies RF (Radio Frequency) stress to predict the lifespan of GaN RF semiconductors, a subject of numerous ongoing domestication studies. Additionally, the study proposes an approach that considers the complex effects of degradation mechanisms in predicting lifespan. When testing the longevity of communication semiconductors, it’s essential to apply RF-input to replicate real-world conditions. The system we developed applies wideband, high power RF stress to individual samples. It monitors RF characteristic changes in real-time and provides independent control of temperature and voltage stress for each sample. This ensures both effective lifespan tests and real-time tracking of semiconductor degradation patterns. Unlike traditional GaAs semiconductors, GaN ones exhibit the compounded influence of degradation mechanisms during RF operation. Therefore, a new lifespan estimation method that identifies the IV characteristic parameters for each degradation mechanism and deduces a relationship between the DC-accelerated life test and the RF-accelerated life test was proposed. The proposed method is significant in that it provides foundational data necessary for the systematic planning of semiconductor reliability testing and the direction of test equipment development. If lifespan tests proceed using this proposed method and data related to degradation mechanisms is derived, it is anticipated to positively impact the future reliability improvement of GaN RF semiconductors.